Contemporary issues in money and banking : essays in honour of Stephen Frowen - Frowen, Stephen F.; Arestis, Philip (Houndmills, Basingstoke, Hampshire : Macmillan Press, 1988)
This book is a collection of essays from scholars on contemporary issues in money and banking in honour of Stephen Frowen. It examined the various implications of financial innovations.
Includes index.
"Stephen Frowen: list of publications": p. 206-210.
Includes bibliographical references.
usc 02/08/2017
Loans
Keywords: Frowen, Stephen F; Money; Banks and banking; Finance